Mi chico latino - Halliwell, Geri; EMI Records (New York : EMI Records, 1999)
Contains two tracks taken from the album Schizophonic. The CD also includes enhanced feature with bonus video Summertime in two different video framesize.
CD 1 : Mi Chico Latino -- G.A.Y. -- Summertime (bonus video).
Koleksi Khas Wiramanja.
To replay video: minimum requirements - Windows 95 PC Pentium 166 or higher processor, 16 MB RAM, Soundblaster compatible sound card, SVGA video card, high colour (16 bit) display, Quad-speed CD-ROM. Loading instructions: Windows 95: Close down all applications and insert the CD-ROM. It will automatically run unless you have disabled the'autorun' feature, in which case, click'start' on the taskbar and select'run', type'd:geri.exe' (where d is the letter of your CD-ROM) and click'ok'. Apple Macintosh Power Mac: Simply insert the CD-ROM into the drive, wait a few seconds and then click on the'Geri' icon. No warranties. This multi-media programme is provided to the user without warranties, express or implied, of any kind. EMI/Chrysalis shall not be liable for any actual or consequential damage arising from the use of, or the inability to use the programme.
Title from disc label.
Keywords: Songs, English